TGF-β inhibitors: the future for prevention and treatment of liver fibrosis? - Wang, Weili; Gao, Yilin; Chen, Yizhen; Cheng, Meng; Sang, Yonghao; Wei, Liuting; Dai, Rong; Wang, Yiping; Zhang, Lei (Frontiers in Immunology, 2025)
Liver fibrosis is a core pathological process in the progression of chronic liver diseases to cirrhosis and hepatocellular carcinoma, characterized by abnormal deposition of extracellular matrix. Transforming growth factor-β (TGF-β), through classical small mothers against decapentaplegic (Smad)-dependent and non-Smad-dependent pathways, activates hepatic stellate cells to transdifferentiate into myofibroblasts, promotes extracellular matrix synthesis, and regulates immunity, serving as a key driver of fibrogenesis. This review systematically summarizes the role of TGF-β in liver fibrosis and details the research progress of TGF-β-targeted inhibitors. Studies show that TGF-β neutralizing antibodies, small molecule receptor antagonists, small molecule signaling inhibitors, and natural compounds and extracts significantly improve experimental liver fibrosis by inhibiting Smad or non-Smad pathways. In clinical trials, drugs such as Pirfenidone and Hydronidone have demonstrated potential for fibrosis reversal in patients with chronic hepatitis. Although TGF-β-targeted therapy has made breakthroughs in basic research and clinical translation, future studies need to focus on multi-target drug design, personalized treatment regimens, and novel delivery systems to accelerate the transition from preclinical research to clinical application, providing innovative therapeutic strategies for liver fibrosis and related liver diseases.